2009
DOI: 10.1016/j.virusres.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Murine norovirus-1 entry into permissive macrophages and dendritic cells is pH-independent

Abstract: SummaryMurine norovirus (MNV) is a recently discovered mouse pathogen. Unlike the fastidious human noroviruses that cause the overwhelming majority of non-bacterial gastroenteritis worldwide, MNV readily infects cells in culture. Its replication in primary murine macrophages and dendritic cells and their derived cell lines allows the study of norovirus cell entry for the first time. In this study we determined the role of pH during MNV-1 infection since the low pH environment of endosomes often triggers uncoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 35 publications
5
45
1
Order By: Relevance
“…Two previous reports have suggested roles for actin in the replication cycle of Caliciviruses; however, the observations are conflicting. Perry et al (38) observed that treatment with cytochalasin D enhanced MNV-1 infection, whereas Stuart and Brown (48) observed that feline calicivirus infection was impaired. In each case, though, only virus-positive cells were enumerated and effects on virus replication were not quantitated.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous reports have suggested roles for actin in the replication cycle of Caliciviruses; however, the observations are conflicting. Perry et al (38) observed that treatment with cytochalasin D enhanced MNV-1 infection, whereas Stuart and Brown (48) observed that feline calicivirus infection was impaired. In each case, though, only virus-positive cells were enumerated and effects on virus replication were not quantitated.…”
Section: Discussionmentioning
confidence: 99%
“…BHK cells engineered to express T7 RNA polymerase (BSR-T7 cells, obtained from Karl-Klaus Conzelmann, Ludwig Maximilian University, Munich, Germany) were maintained in DMEM containing 10% FCS, penicillin (100 SI units/ml), streptomycin (100 g/ml), and 0.5 mg/ml G418. The cDNA clone pT7: MNV 3= RZ, containing the WT MNV-1 genome under the control of a truncated T7 polymerase promoter, and a modified version that contains a frameshift in the NS7 region of ORF1 (pT7:MNV 3= RZ F/S) were previously constructed (48).…”
Section: Methodsmentioning
confidence: 99%
“…MNV has also been isolated from wild mice, confirming its widespread distribution (59). Studies with MNV have begun to probe various aspects of the norovirus replication cycle, including entry mechanisms and attachment factors (24,48,49,67), viral protein function (8,19,30,43,64,66), determinants of virulence (7), and host immune responses (14, 15, 42); however, our understanding of the molecular mechanisms of norovirus genome translation and replication lags far behind that for other RNA viruses.MNV is a positive-sense single-stranded RNA virus with a genome of approximately 7.4 kb covalently attached to a viral genome-linked protein (VPg) at the 5= end and polyadenylated at the 3= end (33). The 5= and 3= untranslated regions (UTRs) are extremely short, 5 and 78 nucleotides (nt), respectively, for MNV-1 (33).…”
mentioning
confidence: 99%
“…MNV-1 and S99 binding to murine macrophages is dependent on terminal sialic acid residues of the ganglioside GD1a, N-linked, or O-linked glycoproteins, while CR3 binding requires only N-linked glycoproteins (21,22). Although multiple studies have elucidated aspects of the multistep process by which MNV enters permissive macrophages (21)(22)(23)(24)(25), how the virus crosses the intestinal epithelial barrier to reach susceptible macrophages and dendritic cells in the first place is unknown.…”
mentioning
confidence: 99%